IMPLIKASI GAYA KEPEMIMPINAN KLINIK PRATAMA NUR’ANNISA KARAWANG - Indah Hoirunniza; Asep Jamaludin; Nandang Nandang (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract The purpose of this study was to provide a description of the leadership style applied at the Pratama Clinic Nur'annisa Karawang. This type of research uses descriptive research. Data collection techniques were carried out by observation through practical work programs, interviews and literature studies. The results of the research obtained are that the leadership style applied at the Pratama Nur'annisa Clinic is a democratic leadership style. This is in accordance with the characteristics of a democratic leadership style such as; decisions are made jointly by the Head of the Clinic and employees, the leader always asks for advice and provides opportunities for employees to make a decision. The head of the clinic provides verbal motivation, praise and criticism. Communication that takes place is reciprocal, both between the Head of the Clinic and employees, as well as between employees and other employees. Opportunities openly for employees to provide suggestions, opinions and criticism. The Head of the Clinic is willing to delegate some of his authority to employees. The Head of the Clinic is willing to delegate some of his authority to the employees and the responsibility for the success of the organization is shared. Abstrak: Tujuan penelitian ini adalah untuk memberikan deskripsi mengenai gaya kepemimpinan yang diterapkan di Klinik Pratama Nur’annisa Karawang. Jenis penelitian ini menggunakan penelitian deskriptif. Teknik pengumpulan data yang dilakukan dengan observasi melalui program kerja praktek, wawancara dan studi literatur. Hasil penelitian yang diperoleh yaitu gaya kepemimpinan yang diterapkan di Klinik Pratama Nur’annisa ini adalah gaya kepemimpinan demokratis. Hal ini sesuai dengan ciri-ciri gaya kepemimpinan demokratis seperti; keputusan dibuat bersama-sama oleh Kepala Klinik dan karyawan, pemimpin selalu meminta saran dan memberikan kesempatan kepada karyawan dalam mengambil suatu keputusan. Kepala Klinik memberikan motivasi secara lisan, pujian dan kritik. Komunikasi yang berlangsung secara timbal balik, baik terjadi antara Kepala Klinik dengan karyawan, maupun antara karyawan dengan karyawan lain. Kesempatan secara terbuka bagi karyawan untuk memberikan saran, pendapat dan kritik. Kepala Klinik bersedia melimpahkan sebagian wewenangnya kepada karyawan. Kepala Klinik bersedia melimpahkan sebagian wewenangnya kepada karyawan dan tanggung jawab akan keberhasilan organisasi dipikul bersama.